PENGARUH STORE ATMOSPHERE, KUALITAS PELAYANAN DAN KEBERAGAMAN PRODUK TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pelanggan Kafe Kopi TM 100 Kabupaten Batu Bara) - Dedy Dwi Arseto (JURNAL ILMIAH EDUNOMIKA, 2023)
This research aims to find out more clearly the influence of Store Atmosphere, Service Quality and Product Diversity on Customer Loyalty with Customer Satisfaction as an Intervening Variable (Case Study of TM 100 Coffee Cafe Customers, Batu Bara Regency). This research uses quantitative methods. This type of research is explanatory research which explains the causal relationship between variables by testing hypotheses. The sample used in this research was 79 respondents using an accidental sampling method with the characteristics of customers who had made purchases at the TM 100 Coffee Café. Data analysis in this research uses Validity Test, Reliability Test, Hypothesis Test (t test). The data processing program in this research uses the Smart PLS software program version 3.0. The research results show that store atmosphere influences customer satisfaction. Service quality has no effect customer satisfaction. Product diversity has no effect customer satisfaction. Store atmosphere has no effect customer loyalty. Service quality has no effect customer loyalty. Product diversity has no effect has an effect on customer loyalty. Customer satisfaction has an effect on customer loyalty. Store atmosphere has an effect on customer loyalty through customer satisfaction as an intervening variable. Service quality has no effect on customer loyalty through customer satisfaction as a variable intervening. Product diversity has no effect on customer loyalty through customer satisfaction as an intervening variable. Keywords : Consumer Loyalty, Consumer Satisfaction, Store Atmosphere, Service Quality, Product Diversity